Farm response of tomato genotypes to Fusarium oxysporum f. sp. lycopersici under controlled pot conditions - Kumari, S; Snehashish, C; Satish, K Y; Smita, K; Kishan, S (Plant Science Today, 2026)
Fusarium wilt of tomato, caused by Fusarium oxysporum f. sp. lycopersici (FOL), is one of the most important and widespread diseases of cultivated tomato. Pot screening experiment was conducted to evaluate 60 tomato genotypes for resistance against FOL the causal agent of Fusarium wilt, under controlled conditions. The experiment was carried out during the Rabi seasons of 2018-19 and 2019-20 in the screenhouse of the Department of Plant Pathology, School of Agriculture, Lovely Professional University, Phagwara. The trials were laid out in a completely randomized design (CRD) with three replications for each genotype. The pathogen inoculum was prepared and introduced into sterilized soil prior to sowing. Data were recorded on wilt incidence, plant height, chlorophyll content and nutritional quality parameters, including vitamin A, lycopene and ascorbic acid content. Results showed significant variation among genotypes for all measured traits. Wilt incidence ranged from 16.7 % in genotype D1 to 50 % in H3, H7 and P3. Genotypes D1, D2 and S Kanchan exhibited moderate resistance. Jaya Hybrid recorded the highest plant height (55.36 cm), while Arka Vikas showed superior chlorophyll content. Nutritionally, D5 and D2 had the highest vitamin A, D4 and D2 were richest in lycopene and D1 recorded maximum ascorbic acid. Based on combined disease resistance and nutritional quality, genotypes D1, D2, D4 and Arka Vikas were identified as promising for future breeding programs and field evaluations.